FK228 Analogues Induce Fetal Hemoglobin in Human Erythroid Progenitors - Levi Makala; Salvatore Di Maro; Tzu-Fang Lou; Sharanya Sivanand; Jung-Mo Ahn; Betty S. Pace (Anemia)
Fetal hemoglobin (HbF) improves the clinical severity of sickle cell disease (SCD), therefore, research to identify HbF-inducing agents for treatment purposes is desirable. The focus of our study is to investigate the ability of FK228 analogues to induce HbF using a novel KU812 dual-luciferase reporter system. Molecular modeling studies showed that the structure of twenty FK228 analogues with isosteric substitutions did not disturb the global structure of the molecule. Using the dual-luciferase system, a subgroup of FK228 analogues was shown to be inducers of HbF at nanomolar concentrations. To determine the physiological relevance of these compounds, studies in primary erythroid progenitors confirmed that JMA26 and JMA33 activated HbF synthesis at levels comparable to FK228 with low cellular toxicity. These data support our lead compounds as potential therapeutic agents for further development in the treatment of SCD.